A SYSTEMATIC REVIEW OF ENVIRONMENTAL LEGISLATION AND POLITICS REGARDING THE REGULATION OF DEVELOPING CONTAMINANTS IN INDONESIA - Firnandes, Banokta; Ramlan, Ramlan; Syahrial, Syahrial; Asnizar, Andi; R, Dony.; S, Herman.; Rafli, M.; Fikri, KMS Novyar Satriawan (International Journal of Multidisciplinary Research and Literature, 2025)
A systematic evaluation of the environmental regulations that apply to emerging pollutants at the international level, with a particular focus on Indonesia, is to be conducted. The search for articles and documents was conducted according to the PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) in databases including PubMed, Scopus, ScienceDirect, Jane’s, Dimensions, Google Scholar, and the Comprehensive System of Standards and Evaluation of the Indonesian Ministry of the Interior. A total of 3089 documents were examined, and based on the inclusion, exclusion, and quality criteria, two tables were created: the first comprising 24 scientific publications and the second containing 7 Indonesian standards. The regulation of developing contaminants is a crucial matter that necessitates the involvement of many sectors, including political, economic, social, and environmental domains. To achieve this, it is essential to coordinate the government and society while taking into account the experiences of other nations for its execution. The challenges related to access to information and educational programs significantly affect compliance with environmental standards, and there is a paucity of scientific knowledge regarding this topic